(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we introduce λ_(s,φ,ψ,L)-generalized Berinde type contraction and obtain some common fixed point results for such class of contractions the setting of triangular α-admissible mappings with respect to η in the framework of b-metric spaces. Our results generalize and extend some theorems in the literature. An example is given to support our result.